Nanometer multi-level natural enzyme hydrogel and preparation method thereof
The construction of nano multi-level natural enzyme hydrogels through polymerization-induced self-assembly technology solves the problems of natural enzyme stability and cascade catalysis, and achieves efficient enzyme protection and biomedical applications.
Patent Information
- Application Number
- CN202411180594.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The application of natural enzymes in the biomedical field has problems such as poor stability and difficult to achieve cascade catalysis, especially at low concentrations, which limits their conversion and application in materials.
Using polymerization-induced self-assembly technology, nano multi-layer natural enzyme hydrogel is constructed to form high-concentration micro-nano assembly to achieve enzyme protection and grade Co-catalysis.
The stability protection and cascade catalytic effect of natural enzymes is achieved, the modification and protection process of enzymes is simplified, and its application prospects in the field of biomedical sciences are improved.
Smart Images

Figure CN119157824A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials and biomedical materials, and in particular to a nano multi-level natural enzyme hydrogel and a preparation method thereof. Background Art
[0002] Hydrogels are generally three-dimensional cross-linked network materials formed by hydrophilic polymers under covalent or non-covalent action. They have excellent properties, including mechanical properties compatible with biological tissues and excellent water retention capacity. They can keep wounds moist and continuously absorb exudate. In addition to sealing wounds to prevent fluid loss and accumulation of purulent substances, they can also prevent scab organisms from promoting bacterial growth and infection. In addition, their timely biodegradation avoids secondary damage during dressing changes, making them ideal wound dressing materials. More importantly, through design and functional integration in structure and physicochemical properties, hydrogels can be given a wide range of biological functions, such as anti-inflammatory, antioxidant, antibacterial and regulation of cell behavior, while improving the microenvironment of chronic wounds and promoting tissue regeneration. At present, a large number of hydrophilic (including natural) polymers can be used to construct hydrogel materials with multiple functions through physical or chemical cross-linking.
[0003] Enzymes are protein macromolecules with biocatalytic activity and excellent biocompatibility. The rejection reactions and side effects caused by them are far lower than those of conventional drugs. At present, many enzyme macromolecules such as glucose oxidase and catalase have shown good effects in promoting wound healing. For example, lysozyme can destroy the β-1,4 glycosidic bond between N-acetylmuramic acid and N-acetylglucosamine in the cell wall, decomposing the insoluble mucopolysaccharides in the cell wall into soluble glycopeptides, causing the cell wall to rupture and the contents to escape, thereby dissolving the bacteria. Glucose oxidase can use glucose to produce reactive oxygen species (ROS), achieving antibacterial effects on bacterially infected wounds. It can also cascade catalyze with catalase to further decompose excess ROS into water and oxygen, reducing the risk of wound inflammation.
[0004] However, there are also certain problems in the application of natural enzymes in the biomedical field. For example, natural enzymes are easy to decompose and have poor stability, which is not conducive to long-term solution storage and efficacy. In addition, the mutual synergistic enhancement and cascade catalysis between multiple enzymes are difficult to achieve at low concentrations, which limits the conversion of natural enzyme-based materials. At present, a series of methods such as polyvinyl alcohol modification and other strategies are used to modify natural enzymes to overcome their stability limitations. However, chemical coupling has a potential impact on enzyme function. At the same time, the modification process is complicated, and the spatial distance of the cascade reaction is also limited. Therefore, how to ensure the functionality of natural enzymes while simplifying the modification and protection strategies of enzymes can provide a good strategy for realizing the cascade reaction of natural enzymes in various biomedical fields.
[0005] Biological bodies have natural nano-multi-layer hierarchical structures. For example, the skin structure is mainly divided into three layers: epidermis, dermis, and subcutaneous tissue. Based on this, the bionic development of nanostructured hydrogels with nano-multi-layer hierarchical structures can achieve better biocompatibility and exert the effects of materials of different dimensions. The strategy for constructing polymer hydrogels with nanostructures usually uses a two-step method, namely constructing loaded nanoparticles and constructing gel carriers. However, hydrogels constructed in this way are limited by the concentration of nanoparticles, and the time consumed is relatively long and the process is relatively complicated. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a nano multi-level natural enzyme hydrogel. Polymerization-induced self-assembly (PISA) is a cutting-edge polymer self-assembly technology that can construct a variety of polymer micro-nano assembly materials in one step through the spontaneous assembly behavior of monomers in the polymerization process. This method has the advantages of high efficiency and convenience, and is particularly easy to achieve high-concentration nano assemblies. The present invention utilizes a polymerization-induced assembly system to protect and further assemble biological enzyme catalysts with poor stability through in-situ self-assembly, thereby realizing a step-by-step assembly process from nanometers to micrometers to macroscopic, and synthesizing a therapeutic enzyme-loaded micro-nano assembly gel with size-selective permeability in one step.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] In the first aspect, the present invention provides a nano multi-layered natural enzyme hydrogel, which is prepared from organic monomers, polyethylene macromolecular chain transfer agent (PEG macro-CTA), and natural enzymes through reversible addition-fragmentation chain transfer free radical polymerization (Reversible Addition-Fragmentation Chain Transfer Polymerization, RAFT) and polymerization induced self-assembly (PISA) method.
[0009] During the preparation process of the nano multi-level natural enzyme hydrogel, micro-nano assemblies encapsulating natural enzymes are formed, and the micro-nano assemblies encapsulating natural enzymes form a multi-level physical gel through entanglement and interaction, that is, a nano multi-level natural enzyme hydrogel of physical gel is obtained, and the nano multi-level natural enzyme hydrogel has a high concentration of micro-nano assemblies encapsulating natural enzymes inside.
[0010] The polyethylene macromolecular chain transfer agent is a polyethylene glycol trithioester derivative RAFT agent, which is obtained by esterification reaction of polyethylene glycol monomethyl ether and a carboxyl-containing RAFT agent.
[0011] Specifically, the carboxyl-containing RAFT agent is 4-cyano-4-[[(ethylthio)thioxomethyl]thio]pentanoic acid (CEPA); and the organic monomer is N-(2-hydroxypropyl)methacrylamide (HPMA).
[0012] Specifically, the natural enzymes include but are not limited to glucose oxidase (Gox), catalase (CAT), horseradish peroxidase (HRP), superoxide dismutase, peroxidase, and the like.
[0013] Preferably, the natural enzyme is a combination of two or more enzymes with a cascade effect between them, and the nano multi-layered natural enzyme hydrogel has the performance of protecting the cascade effect of the enzyme, can ensure the cascade effect of the enzyme in the system, and protect the enzyme; in a preferred embodiment, the natural enzyme is a combination of glucose oxidase and catalase.
[0014] In a second aspect, the present invention also provides a method for preparing the above-mentioned nano multi-level natural enzyme hydrogel, comprising the following steps: dissolving polyethylene macromolecular chain transfer agent (PEG macro-CTA), N-(2-hydroxypropyl) methacrylamide (HPMA), and natural enzyme in water to obtain a polymer mixture, degassing the polymer mixture with an inert gas, and reacting it in a photoreactor under light with a wavelength of 405 nm to obtain a nano multi-level natural enzyme hydrogel.
[0015] Specifically, the preparation process of the polyethylene macromolecular chain transfer agent is: dissolving polyethylene glycol monomethyl ether, 4-dimethylaminopyridine (DMAP), CEPA, and N,N-dicyclohexylcarbodiimide (DCC) in a good solvent, stirring the reaction, filtering and rotary evaporating, and precipitating with a poor solvent to obtain an initiator.
[0016] Specifically, in the preparation process of the polyethylene macromolecular chain transfer agent, the good solvent used is anhydrous dichloromethane (DCM), and the poor solvent used is anhydrous ether.
[0017] Furthermore, the preparation process of the polyethylene macromolecular chain transfer agent is as follows: polyethylene glycol monomethyl ether, CEPA, and DMAP are placed in a sealed flask, and under nitrogen protection, DCC dissolved in DCM is added, dissolved, and stirred for 48-60 hours, during which DCC is added, filtered, concentrated and filtered by rotary evaporation, and the product is placed in ether for precipitation, and then the precipitate is placed in a fume hood environment for drying, and finally vacuum dried for 12-24 hours to obtain the product polyethylene macromolecular chain transfer agent PEG-CEPA macro-CTA.
[0018] In order to optimize the catalytic performance and gelling performance of the system, through bioorthogonal experimental design, in the polymer mixture, the equivalent ratio of N-(2-hydroxypropyl) methacrylamide (HPMA) and polyethylene macromolecular chain transfer agent (PEG-CEPA macro-CTA) is 300:1 to 900:1, the mass ratio of each natural enzyme to the polyethylene macromolecular chain transfer agent is 1:3000 to 1:15, and the mass concentration ratio of N-(2-hydroxypropyl) methacrylamide is 10%-70%.
[0019] Specifically, the inert gas used in the method for preparing the enzyme nano multi-level natural enzyme hydrogel is nitrogen, argon, etc.
[0020] In a preferred embodiment, the natural enzyme is a combination of glucose oxidase and catalase. In the polymer mixture, the equivalent ratio of N-(2-hydroxypropyl)methacrylamide and polyethylene macromolecular chain transfer agent is 400:1, the mass ratio of glucose oxidase, catalase and polyethylene macromolecular chain transfer agent is 1:60, and the mass concentration ratio of N-(2-hydroxypropyl)methacrylamide is 60%.
[0021] Furthermore, the preparation method of the enzyme nano multi-level natural enzyme hydrogel is as follows: PEG-CEPA macro-CTA, CAT and GOx are completely dissolved and mixed in water, HPMA is added, vortexed and mixed, sealed, an inert gas is introduced to exhaust the air in the system, the ventilation time is about 20-30 minutes, and then placed in a photoreactor for reaction, the light wavelength is set to 405nm, the rotation speed is 800rpm, and the reaction is performed for 3 hours. After the reaction is completed, the sealing rubber stopper is opened, contacted with air, vortexed, and the reaction is terminated.
[0022] The present invention has the following beneficial effects:
[0023] The nano multi-level natural enzyme hydrogel provided by the present invention is a nano multi-level hydrogel that forms an enzyme-loaded nanometer by in-situ reaction of a high molecular polymer and a natural enzyme through a polymerization-induced assembly system, and in-situ self-assembly forms a micro-nano assembly during the polymerization reaction, and the formed micro-nano assembly forms a nano multi-level physical gel by entanglement and interaction. This physical gel has a high-concentration micro-nano assembly structure, and a high-concentration, stable natural enzyme-loaded assembly can be achieved by adding natural enzymes and further forming a hydrogel. This simple, in-situ, mild in-situ natural enzyme protection method can ensure the mutual series reaction between multiple enzymes, and can protect the stability of natural enzymes at the same time. In addition, this nano multi-level hydrogel is prepared and realized in one step from micro to macro, with simple ingredients and mild conditions, and will have a good application prospect in the field of biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The figure is a schematic diagram of the preparation of the nano multi-level natural enzyme hydrogel of the present invention;
[0025] Figure 2 The molecular weight results of gel chromatography characterization of Preparation Example 1;
[0026] Figure 3 The UV response peak result (309 nm) of Preparation Example 1;
[0027] Figure 4 This is a physical morphology photo of the nano multi-level natural enzyme hydrogel PHCG@Gel prepared in Example 1;
[0028] Figure 5 This is a physical morphology photo of the fluorescently modified nano-multilayered natural enzyme hydrogel PHCG@Gel prepared in Example 2;
[0029] Figure 6 The transmission electron microscopy characterization image of the PHCG assembly prepared in Preparation Example 4;
[0030] Figure 7 This is a transmission electron microscopy characterization image of the PHC assembly prepared in Preparation Example 7;
[0031] Figure 8 The transmission electron microscopy characterization image of the PHCG assembly prepared in Example 1;
[0032] Fig. 9 The ultraviolet absorption peak diagram of fluorescently modified CAT and GOx prepared in Preparation Example 2;
[0033] Fig.10 This is a confocal microscopy characterization image of the fluorescently modified PHCG assembly prepared in Preparation Example 5;
[0034] Fig.11 The fluorescence spectra of the fluorescently modified CAT and GOx prepared in Preparation Example 2;
[0035] Fig.12 The fluorescence spectrum of the fluorescently modified PHCG assembly prepared in Preparation Example 5;
[0036] Fig.13 This is a three-dimensional image of the fluorescently modified PHCG@Gel prepared in Example 2 under a confocal microscope;
[0037] Fig.14 Schematic diagram of the principle for evaluating glucose oxidase GOx and cascade enzyme activity;
[0038] Fig.15 This is a diagram showing the GOx enzyme activity verification result of the PHG assembly prepared in Preparation Example 6;
[0039] Fig.16This is a diagram showing the CAT enzyme activity verification result of the PHC assembly prepared in Preparation Example 7;
[0040] Fig.17 This is a test diagram of the GOx and CAT cascade enzyme effects of the PHCG assembly prepared in Preparation Example 4;
[0041] Fig.18 This is a diagram showing the evaluation results of the protection effect of the PHCG assembly prepared in Preparation Example 4 on the enzyme activity;
[0042] Fig.19 This is the physical morphology of PHCG@Gel prepared in Example 1 under a scanning electron microscope. DETAILED DESCRIPTION
[0043] The technical scheme of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in the art or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0044] The embodiments of the present invention are as follows, which are intended to further describe the present invention in detail. It should be noted that the following examples are only examples within a suitable range, wherein specific process parameters, etc. are only for reference, and are not intended to be limited to the specific values exemplified below. Those skilled in the art can select parameters within a suitable range according to actual needs through the description herein.
[0045] See also Figure 1 The nano multi-level natural enzyme hydrogel of the present invention is a nano multi-level hydrogel loaded with natural enzymes formed by in-situ reaction of high molecular polymers and natural enzymes through a polymerization-induced assembly system. In the polymerization reaction process, the in-situ self-assembles to form a micro-nano assembly that encapsulates the natural enzyme. The formed micro-nano assembly forms a nano multi-level physical gel through entanglement and interaction, that is, a physical gel that encapsulates the enzyme is formed by in-situ reaction assembly. This simple, in-situ, mild in-situ natural enzyme protection method ensures the mutual series reaction between multiple enzymes and protects the stability of the enzyme. The formation of a physical gel network can realize controllability of the site where the enzyme acts, achieve specificity, and reduce the side effects that may be caused in its application.
[0046] Preparation Example 1 Synthesis of PEG-CEPA macro-CTA
[0047] Place polyethylene glycol monomethyl ether, CEPA and DMAP in a glass bottle, seal it, add DCC and DCM, stir for 48-60 hours, add DCC during the period, filter, concentrate by rotary evaporation, filter and precipitate the reactant in ether for 3 times, finally dry the precipitate by ventilation and vacuum drying to obtain PEG-CEPA macro-CTA. Figure 2-3 As shown, the molecular weight test results of gel chromatography and the UV test results show the successful synthesis of the polyethylene macromolecular chain transfer agent PEG-CEPA macro-CTA in this preparation example.
[0048] Preparation Example 2 CAT and GOx enzyme solutions with fluorescence modification
[0049] Take 50 μL of succinimidyl ester (BODIPY-FL NHS) dye solution (20 mM) and mix it with 5 mL of CAT enzyme solution (8 mg / mL), and take another 60 μL of boron dipyrromethene dye (BODIPY-R6G NHS) dye solution (20 mM) and mix it with 3 mL of GOx enzyme solution (7 mg / mL), stir it for 12 hours, and then dialyze it to obtain CAT enzyme solution with fluorescence modification and GOx enzyme solution with fluorescence modification.
[0050] Preparation Example 3 Preparation of PEG-HPMA assembly solution system
[0051] Take PEG-CEPAmacro-CTA0.03g obtained in Preparation Example 1, dissolve in 0.61mL water, add 0.326mL HPMA, mix thoroughly, pass nitrogen to discharge the air in the system, ventilation time is about 20 minutes, airtight, then placed in a photoreactor, set the light wavelength 405nm, speed 800rpm, react for 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain the polymer assembly solution system formed by PEG-HPMA. Tyndall phenomenon can be observed under laser irradiation, indicating that the system is successfully synthesized.
[0052] Preparation Example 4 Preparation of PHCG Assembly
[0053] Take 0.03g of PEG-CEPA macro-CTA obtained in Preparation Example 1, mix it thoroughly with 0.2mL GOx enzyme solution (8mg / mL) and 0.05mL CAT enzyme solution (200,000 U / mL), dissolve it in 0.36mL water, add 0.326mL HPMA, mix it thoroughly, pass nitrogen into the air in the system, and the ventilation time is about 20 minutes. It is sealed and then placed in a photoreactor for reaction, and the light wavelength is set to 405nm, the speed is 800rpm, and the reaction is performed for 3 hours. After the reaction is completed, the sealing rubber stopper is opened, contacted with air, vortexed, and the reaction is terminated to obtain an enzyme-encapsulated polymer assembly solution, wherein the assembly is recorded as PHCG nanoassembly.
[0054] Preparation Example 5 Preparation of PHCG assembly with fluorescence modification
[0055] Take 0.03g of PEG-CEPA macro-CTA prepared in Preparation Example 1, 0.143mL of GOx enzyme solution (7mg / mL) and 0.125mL of CAT enzyme solution (8mg / mL) with fluorescence modification prepared in Preparation Example 2, dissolve in 0.342mL of water, add 0.326mL of HPMA, mix thoroughly, introduce nitrogen to discharge the air in the system, the ventilation time is about 20 minutes, airtight, then place in a photoreactor for reaction, set the light wavelength to 405nm, the speed is 800rpm, and the reaction is 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain a solution of a polymer assembly of enzyme package with fluorescence modification, wherein the assembly is recorded as a PHCG nano assembly with fluorescence modification.
[0056] Preparation Example 6 Preparation of PHG Assembly
[0057] Take 0.03g of PEG-CEPA macro-CTA prepared in Preparation Example 1, add 2mg GOx and 0.61mL water, wait until the system is dissolved, wait until the system is dissolved, add 0.326mL of HPMA, mix thoroughly, pass nitrogen to exhaust the air in the system, the ventilation time is about 20 minutes, close, and then place in a photoreactor for reaction, set the light wavelength to 405nm, the speed to 800rpm, and react for 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain an enzyme-encapsulated polymer assembly solution, in which the assembly is recorded as PHG nanoassembly.
[0058] Preparation Example 7 Preparation of PHC Assembly
[0059] Take 0.03g of PEG-CEPA macro-CTA obtained in Preparation Example 1, add 0.05mL CAT enzyme solution (200,000 U / mL) and 0.56mL water, wait until the system is dissolved, wait until the system is dissolved, add 0.326mL of HPMA, mix thoroughly, pass nitrogen to discharge the air in the system, the ventilation time is about 20 minutes, airtight, then place in a photoreactor to react, set the light wavelength to 405nm, the speed is 800rpm, and the reaction is 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain an enzyme-encapsulated polymer assembly solution, wherein the assembly is recorded as PHC nanoassembly.
[0060] Preparation Example 8 Preparation of PHG assembly with fluorescence modification
[0061] Take 0.03g of PEG-CEPA macro-CTA obtained in Preparation Example 1, add 0.143mL of the enzyme GOx (7mg / mL) with fluorescence modification obtained in Preparation Example 2, 0.467mL of water, and after the system is dissolved, add 0.326mL of HPMA, mix thoroughly, pass nitrogen to discharge the air in the system, the ventilation time is about 20 minutes, close, and then place in a photoreactor to react, set the light wavelength to 405nm, the speed to 800rpm, and react for 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain a solution of a polymer assembly of an enzyme package with fluorescence modification, wherein the assembly is recorded as a PHG nanoassembly with fluorescence modification.
[0062] Preparation Example 9 Preparation of Fluorescently Modified PHC Assembly Solution
[0063] Take PEG-CEPA macro-CTA0.03g obtained in Preparation Example 1, add CAT enzyme solution (8mg / mL) 0.125mL and 0.485mL water with fluorescence modification obtained in the corresponding Preparation Example 2, after the system is dissolved, add 0.326mL HPMA, mix thoroughly, introduce nitrogen to discharge the air in the system, the ventilation time is about 20 minutes, airtight, then place in a photoreactor to react, set the light wavelength to 405nm, the speed is 800rpm, and the reaction is 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain a solution of a fluorescently modified enzyme-encapsulated polymer assembly, wherein the assembly is recorded as a fluorescently modified PHC nanoassembly.
[0064] Example 1 Preparation of enzyme-encapsulated gel PHCG@Gel
[0065] Take 0.03g of PEG-CEPA macro-CTA prepared in Preparation Example 1, mix it thoroughly with 0.1mL GOx enzyme solution (5mg / mL) and 0.1mL CAT enzyme solution (5mg / mL), dissolve it in 0.41mL water, add 0.326mL HPMA, mix it thoroughly, pass nitrogen to exhaust the air in the system, and ventilate it for about 20 minutes. Then seal it and place it in a photoreactor to react. Set the light wavelength to 405nm and the speed to 800rpm for 3 hours. After the reaction is completed, open the sealing rubber stopper, contact it with air, vortex it, terminate the reaction, and obtain a nano multi-level natural enzyme hydrogel, which is recorded as PHCG@Gel. Its physical morphology is as follows Figure 4 shown.
[0066] Example 2 Preparation of enzyme-encapsulated gel PHCG@Gel with fluorescence modification
[0067] Take 0.03g of PEG-CEPA macro-CTA prepared in Preparation Example 1, 0.071mL (7mg / mL) of GOx enzyme solution with fluorescence modification prepared in Preparation Example 2, and 0.063mL (8mg / mL) of CAT fluorescent enzyme solution, dissolve in 0.476mL of water, add 0.326mL of HPMA, mix thoroughly, introduce nitrogen to exhaust the air in the system, and ventilate for about 20 minutes. Then seal it and place it in a photoreactor for reaction. Set the light wavelength to 405nm, the speed to 800rpm, and react for 3 hours. After the reaction is completed, open the sealing rubber stopper, contact with air, vortex, terminate the reaction, and obtain a nano multi-level natural enzyme hydrogel with fluorescence modification, denoted as PHCG@Gel, and its physical morphology is as follows Figure 5 shown.
[0068] <Performance Test>
[0069] (1) Transmission electron microscopy observation of the physical morphology of assemblies with different enzyme amounts
[0070] 10 μL of each of the enzyme-encapsulated nanoassembly solution prepared in Preparation Example 4 and Preparation Example 7 and the enzyme-encapsulated gel prepared in Example 1 were dispersed on the carbon film surface of the copper mesh and then dried for transmission electron microscopy characterization. The results are as follows: Figure 6-8 shown.
[0071] Depend on Figure 6-8 It can be observed that the polymer and the natural enzyme form enzyme-encapsulated nanoassemblies through polymerization-induced self-assembly, which is conducive to the formation of a more three-dimensional gel structure and presents a morphological transformation from microspheres and vesicles to worm-like structures. In addition, it can be observed that when the system forms a gel in one step in situ, the number of worm-like assemblies inside it increases significantly, indicating that worm-like assemblies are conducive to the formation of physical gels during in situ assembly.
[0072] (2) UV spectrophotometer verification of fluorescence modification of GOx and CAT enzymes
[0073] Take 2 mL of the CAT and GOx enzyme solutions prepared in Preparation Example 2 respectively, and detect their corresponding response peaks under a UV spectrophotometer, with water as the standard baseline solution. The results are as follows: Fig. 9 show.
[0074] Depend on Fig. 9 It can be seen that the CAT and GOx prepared in Preparation Example 2 have response peaks at about 503 nm and 522 nm, respectively, indicating that the fluorescent groups are successfully modified on the corresponding CAT and GOx enzyme protein structures.
[0075] (3) Confocal microscopy analysis to observe the distribution of enzymes in PHCG assemblies
[0076] Take 10 μL of the fluorescently modified PHCG assembly solution prepared in Preparation Example 5, drop it on a glass slide, cover it with a coverslip, evaporate it overnight at room temperature, seal the slide and store the sample for confocal imaging. The results are as follows: Fig.10 shown.
[0077] Depend on Fig.10 It can be observed that compared with the control group (the CAT and GOx enzyme solution mixture prepared in Preparation Example 2), the CAT and GOx in the PHCG assembly are co-localized, indicating that CAT and GOx are encapsulated in the nanoassembly formed by the system.
[0078] (4) Fluorescence spectroscopy to detect enzyme localization in PHCG-encapsulated vesicles
[0079] Take 1 mL of the fluorescently modified CAT and GOx enzyme solutions prepared in Preparation Example 2 respectively in four-sided glass cuvettes and scan their fluorescence spectra under a fluorescence spectrophotometer. The results are as follows: Fig.11 shown.
[0080] Depend on Fig.11 It was shown that the fluorescence spectra of fluorescently modified CAT and GOx overlapped, and fluorescence resonance energy transfer could occur.
[0081] Then, the excitation wavelength was fixed to 495 nm, the excitation wavelength of CAT carrying fluorescence, and the CAT-GOx natural enzyme solution mixed group and the PHCG assembly solution with fluorescence modification prepared in Preparation Example 5 were scanned in the range of 505-650 nm to obtain the corresponding spectra. All the above measurements were carried out under the set instrument conditions: Slit 2.5, Voltage 700 V, Speed 240, and the data were processed to obtain Fig.12 Results shown.
[0082] Depend on Fig.12It was shown that, compared with the natural enzyme solution group, there was a fluorescence resonance energy transfer phenomenon between CAT and GOx in the PHCG nanoassembly solution prepared in Preparation Example 5, indicating that CAT and GOx in Preparation Example 5 were successfully encapsulated in the nanoassembly formed by the polymer.
[0083] (5) Confocal microscopy characterization of PHCG@Gel morphology
[0084] Use tweezers to pick up an appropriate amount of dialyzed PHCG@Gel prepared in Example 2 on a glass slide, cover it with a cover glass, flatten it, and place it at room temperature overnight. The sample is sealed and stored for confocal photography. The photography results are shown in Fig.13 shown.
[0085] Depend on Fig.13 It can be observed that the enzyme with fluorescence modification is evenly distributed in the three-dimensional system, indicating that the enzyme-encapsulated nanoassembly is evenly dispersed in the formed physical gel.
[0086] (6) Verification of GOx enzyme activity of enzyme-encapsulated nanoassembly PHG
[0087] Glucose oxidase GOx can oxidize glucose into gluconic acid and hydrogen peroxide (H2O2). Fig.14 As shown, when the system has H2O2, under the catalysis of horseradish peroxidase (HRP), the fluorescent red dye (Apple Red) can be converted into resorufin with fluorescent characteristics, and the enzyme activity of GOx can be verified by detecting the amount of H2O2. The H2O2 probe Apple Red was prepared into a 20mM system, and the HRP solid powder (300U / mg) was prepared into a 0.4U / mL enzyme solution with phosphate buffer (PBS), and then the probe was diluted 250 times with the HRP enzyme solution. 50μL of 30mg / mL glucose solution was mixed with 100μL of the PHG assembly solution prepared in Preparation Example 6 diluted 200 times, incubated at 37°C for 30 minutes, and then centrifuged at 4°C and 8000rpm for 5 minutes, and 150μL of the supernatant was taken in a 96-well plate. 50μL of the probe-enzyme mixture was added, incubated for 10 minutes, and 2 duplicate wells were set. The fluorescence was detected by a multifunctional microplate reader (the excitation wavelength was set to 530 nm and the scanning wavelength range was 550 nm-620 nm). The same steps were followed to replace the PHG assembly solution of Preparation Example 6 with PBS as a negative control, and a 200-fold diluted natural GOx enzyme solution as a positive control group. The data obtained were analyzed as follows: Fig.15 shown.
[0088] Depend on Fig.15It can be observed that both the PHG group and the natural GOx enzyme solution group have obvious fluorescence values compared with the PBS positive control group, and the fluorescence intensity of the PHG group and the natural GOx enzyme solution group is similar, indicating that the PHG group has better GOx enzyme activity, indicating that the catalytic activity of GOx can still be better exerted when GOx is encapsulated in the nanoassembly.
[0089] (7) Validation of CAT enzyme activity of enzyme-encapsulated nanoassembly PHC
[0090] Prepare a glass bottle with a capacity of 20mL, put in a stirrer, add 10mL 1mM H2O2, insert the probe of the dissolved oxygen meter below the liquid surface and fix it, wait for the reading to stabilize, add the corresponding test system, and observe the change in oxygen generation within 5 minutes. The test system is 25μL, 50μL, and 75μL of the PHC assembly solution prepared in Example 7 diluted 100 times, and 50μL of the natural CAT enzyme solution after illumination. Observe the change in oxygen generation within 5 minutes, the results are as follows Fig.16 show.
[0091] Depend on Fig.16 It can be seen that the PHC assembly has good CAT enzyme activity and is concentration-dependent. The results show that the PHC assembly encapsulating CAT can better exert CAT enzyme activity.
[0092] (8) Verification of the cascade effect of the enzyme-encapsulated assembly
[0093] GOx can oxidize glucose into gluconic acid and H2O2, and CAT catalyzes the decomposition of H2O2. The cascade effect of GOx and CAT can be determined by detecting the intermediate product H2O2. Fig.14 As shown, the cascade effect of GOx and CAT was verified by detecting the amount of H2O2. The Applex Red-HRP probe-enzyme mixed system was prepared as described in the performance test (6), and 100 μL of the PHCG assembly solution prepared in Preparation Example 4 diluted 200 times and the PHG assembly solution prepared in Preparation Example 6 diluted 200 times were taken, respectively, and mixed with 50 μL of glucose solution (30 mg / mL), incubated at 37°C for 30 minutes, and then centrifuged at 4°C and 8000 rpm for 5 minutes. 150 μL of the supernatant was taken from each group and placed in a well plate. Add 50 μL of the probe-enzyme mixture and incubate for 10 minutes. Two replicate wells were set up for each group. Fluorescence was detected under an enzyme reader (the excitation wavelength was set to 530 nm and the scanning wavelength range was 550 nm-620 nm). The PBS group was used as a negative control in the same steps, and the results were analyzed as shown in the following figure. Fig.17 shown.
[0094] Depend on Fig.17It can be observed that the fluorescence intensity of the PHG group was higher, indicating that more H2O2 was generated, while the fluorescence intensity of the PHCG group was significantly lower than that of the PHG group, indicating that part of the H2O2 produced by GOx was catalytically decomposed by CAT, and CAT and GOx in the PHCG assembly were successfully cascaded.
[0095] (9) Verification of the protective performance of the enzyme-encapsulated assembly on enzyme activity
[0096] The GOx natural enzyme solution, the natural enzyme mixture of GOx and CAT, the PHCG assembly solution prepared in Preparation Example 4, and the PHG assembly solution prepared in Preparation Example 6 were placed at room temperature, and their enzyme activities were verified at 0, 1, 2, and 4 weeks after placement. The method for testing the enzyme activity was the same as the method described in "Performance Test (6) and (8)" above, and the product H2O2 of GOx-catalyzed glucose was measured. The fluorescence value ratio was plotted, and the results were shown in Figure 2. Fig.18 show.
[0097] As the placement time increases, it can be observed that the fluorescence intensity difference between the natural GOx enzyme solution group and the PHG group is getting bigger and bigger. There is a difference in the ability of the two to catalyze the production of H2O2, and the PHG group is higher than the natural GOx enzyme solution group, while the fluorescence intensity of the PHCG group is lower than that of the GOx and CAT mixed enzyme solution group, indicating that the PHCG group has a better ability to cascade H2O2 removal than the mixed enzyme solution. The above results show that encapsulating the enzyme in the assembly formed by the polymer is beneficial to protect the enzyme activity to a certain extent and has a certain improvement effect on its cascade effect.
[0098] (10) Scanning electron microscopy observation of the physical morphology of PHCG@Gel
[0099] Take an appropriate amount of PHCG@Gel prepared in Example 1, freeze it at -80°C for 2 hours, and then freeze-dry it in a vacuum freeze dryer for 24 hours. Then take it out, soak it in liquid nitrogen for a few seconds, and freeze-break it to obtain a gel cross section. The cross section is placed upward on a stage with a conductive glue, coated with a carbon film, and the physical morphology of the gel is observed under a scanning electron microscope.
[0100] Fig.19 The physical cross-section of PHCG@Gel prepared in Example 1 under a scanning electron microscope is shown, indicating that the gel has a good reticular porous structure inside.
[0101] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above examples, and various exploration changes can be made according to the invention and creation purpose of the present invention. Any changes, modifications, substitutions, combinations or simplifications made according to the methods and technical contents disclosed in the present invention should be equivalent replacement methods, and all within the spirit and principles of the present invention should be within the scope of the present invention.
Claims
1. A nano multi-level natural enzyme hydrogel, characterized in that: It is prepared from organic monomers, polyethylene macromolecular chain transfer agents, and natural enzymes through reversible addition-fragmentation chain transfer free radical polymerization and polymerization-induced self-assembly. The nano multi-level natural enzyme hydrogel is a physical gel, which has micro-nano assemblies encapsulating natural enzymes inside; The polyethylene macromolecular chain transfer agent is a polyethylene glycol trithioester derivative having a trithioester functional group; and the organic monomer is N-(2-hydroxypropyl) methacrylamide.
2. The nano multi-level natural enzyme hydrogel according to claim 1, characterized in that: The natural enzyme includes one or more combinations of glucose oxidase (Gox), catalase (CAT), horseradish peroxidase (HRP), superoxide dismutase, and peroxidase.
3. The nano multi-level natural enzyme hydrogel according to claim 1, characterized in that: The natural enzyme is a combination of two or more enzymes with a cascade effect between them.
4. The nano multi-level natural enzyme hydrogel according to claim 3, characterized in that: The natural enzyme is a combination of glucose oxidase and catalase.
5. The nano multi-level natural enzyme hydrogel according to claim 1, characterized in that: The polyethylene macromolecular chain transfer agent is obtained by esterification reaction of polyethylene glycol monomethyl ether and a carboxyl-containing RAFT agent, and the carboxyl-containing RAFT agent is 4-cyano-4-[[(ethylthio)thioketomethyl]thio]pentanoic acid.
6. The method for preparing the nano multi-level natural enzyme hydrogel according to claim 1, characterized in that: The steps include: A polyethylene macromolecular chain transfer agent, N-(2-hydroxypropyl) methacrylamide and a natural enzyme are dissolved in water to obtain a polymer mixture, the polymer mixture is degassed with an inert gas, and reacted in a photoreactor under light with a wavelength of 405 nm to obtain a nano multi-level natural enzyme hydrogel.
7. The method for preparing the nano multi-level natural enzyme hydrogel according to claim 6, characterized in that: The preparation process of the polyethylene macromolecular chain transfer agent is as follows: polyethylene glycol monomethyl ether, 4-dimethylaminopyridine, 4-cyano-4-[[(ethylthio)thioketomethyl]thio]pentanoic acid and N,N-dicyclohexylcarbodiimide are dissolved in a good solvent, stirred for reaction, filtered and rotary evaporated, and precipitated with a poor solvent to obtain the polyethylene macromolecular chain transfer agent.
8. The method for preparing the nano multi-level natural enzyme hydrogel according to claim 6, characterized in that: In the polymer mixture, the equivalent ratio of N-(2-hydroxypropyl)methacrylamide to polyethylene macromolecular chain transfer agent is 300:1 to 900:1, the mass ratio of each natural enzyme to polyethylene macromolecular chain transfer agent is 1:3000 to 1:15, and the mass concentration ratio of N-(2-hydroxypropyl)methacrylamide is 10%-70%.
9. The method for preparing the nano multi-level natural enzyme hydrogel according to claim 8, characterized in that: The natural enzyme is a combination of glucose oxidase and catalase. In the polymer mixture, the equivalent ratio of N-(2-hydroxypropyl) methacrylamide to polyethylene macromolecular chain transfer agent is 400:1, the mass ratio of glucose oxidase, catalase and polyethylene macromolecular chain transfer agent is 1:60, and the mass concentration ratio of N-(2-hydroxypropyl) methacrylamide is 60%.
10. The method for preparing the nano multi-level natural enzyme hydrogel according to claim 6, characterized in that: The inert gas used is nitrogen or argon.
Citation Information
Patent Citations
Lipase gel particle and preparation thereof
CN101353654A
Enzyme-macromolecule conjugate and preparing method and application thereof
CN103451174A
Beta-ketone ester functionalized polymeric nano-material and photochemical synthesis method thereof
CN108299590A
Preparation method and application of multi-enzyme active nano-enzyme fluorescent hydrogel
CN115386105A
Cascade enzyme catalysis nano composite material as well as preparation method and application thereof
CN117645992A
